Labelling assessment and molecular authentication of squid-based products from two major European cities - Alice Giusti; Lara Tinacci; Andrea Armani; Gabriele Spatola; Jiajie Hu; Vanya Vulperhorst; Allison L. Perry; Marine Cusa (Food Control, 2026)

Extensive Use of Habitat-Damaging Fishing Gears Inside Habitat-Protecting Marine Protected Areas - Allison L. Perry; Jorge Blanco; Silvia García; Nicolas Fournier (Frontiers in Marine Science, 2022)
Marine protected areas (MPAs) are critical for halting marine biodiversity loss and safeguarding ecosystems. However, efforts to designate additional areas as MPAs have generally taken precedence over ensuring that designated sites are effectively protected. Serious concerns exist about marine “paper parks” in Europe, particularly in relation to the threat of fishing. We focussed on 1,945 MPAs in EU and UK waters that are designated to protect habitats, and assessed the extent of fishing inside them with gears that are known to directly threaten those same habitats. Such “high-risk” fishing was widespread, occurring within 510 MPAs that represented 86% of the area assessed, and was more prevalent in larger, offshore sites. More intense high-risk fishing inside reef and sandbank MPAs was associated with the poorer conservation status of those habitats in countries’ waters. Our findings indicate that without systematic restrictions on damaging fishing gears, MPAs are unlikely to help reverse the ongoing declines of European marine habitats.

Correction to: “Relationships Between Salinity and Short-Term Soil Carbon Accumulation Rates from Marsh Types Across a Landscape in the Mississippi River Delta” - Melissa M. Baustian; Camille L. Stagg; Carey L. Perry; Leland C. Moss; Tim J. B. Carruthers; Mead Allison (Wetlands, 2020)

Untying the Mediterranean Gordian Knot: A Twenty First Century Challenge for Fisheries Management - Ilaria Vielmini; Allison L. Perry; María José Cornax (Frontiers in Marine Science, 2017)

Relationships Between Salinity and Short-Term Soil Carbon Accumulation Rates from Marsh Types Across a Landscape in the Mississippi River Delta - Melissa M. Baustian; Camille L. Stagg; Carey L. Perry; Leland C. Moss; Tim J. B. Carruthers; Mead Allison (Wetlands, 2017)

Vulnerability of national economies to the impacts of climate change on fisheries - Edward H. Allison; Allison L. Perry; Marie‐Caroline Badjeck; W. Neil Adger; Katrina Brown; Declan Conway; Ashley S. Halls; Graham M. Pilling; John D. Reynolds; Neil L. Andrew; Nicholas K. Dulvy (Fish and Fisheries, 2009)
Anthropogenic global warming has significantly influenced physical and biological processes at global and regional scales. The observed and anticipated changes in global climate present significant opportunities and challenges for societies and economies. We compare the vulnerability of 132 national economies to potential climate change impacts on their capture fisheries using an indicator‐based approach. Countries in Central and Western Africa (e.g. Malawi, Guinea, Senegal, and Uganda), Peru and Colombia in north‐western South America, and four tropical Asian countries (Bangladesh, Cambodia, Pakistan, and Yemen) were identified as most vulnerable. This vulnerability was due to the combined effect of predicted warming, the relative importance of fisheries to national economies and diets, and limited societal capacity to adapt to potential impacts and opportunities. Many vulnerable countries were also among the world’s least developed countries whose inhabitants are among the world’s poorest and twice as reliant on fish, which provides 27% of dietary protein compared to 13% in less vulnerable countries. These countries also produce 20% of the world’s fish exports and are in greatest need of adaptation planning to maintain or enhance the contribution that fisheries can make to poverty reduction. Although the precise impacts and direction of climate‐driven change for particular fish stocks and fisheries are uncertain, our analysis suggests they are likely to lead to either increased economic hardship or missed opportunities for development in countries that depend upon fisheries but lack the capacity to adapt.